ANALISIS TINGKAT PEMAHAMAN WASIT JURI KABUPATEN HULU SUNGAI TENGAH TERHADAP PERATURAN TERBARU PERTANDINGAN PENCAK SILAT DALAM KATEGORI TANDING - Muhammad Rizky Abdillah; Norma Anggara; Akhmad Amirudin (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
This research aims to determine the level of understanding of a jury referee in Hulu Sungai Tengah district. This research uses quantitative descriptive methods with a population of 10 jury referees and a sample taken of 5 respondents using the purposive sampling method. The instruments used are surveys, data collection, questionnaires and documentation. The subject of this research is the jury referee for Hulu Sungai Tengah district. The analysis carried out was using a questionnaire distribution technique using Google Form. This research shows that the overall results of the referee's and jury's answers are presented in percentage form. There are 6 indicators studied, including 3 categories of Very High indicators, and 3 categories of High indicators. in terms of weighing procedures 87% Very High, Prohibitions/competition violations 80% Very High, competition categories 80% Very High, Equipment Requirements for Athlete/Pesilat 67%, Techniques used 75%, Warnings and Punishments 60%. All data results mean the understanding level of the referees for the Hulu Sungai Tengah district is 64%, which is included in the high category. Overall, what we can take from the Analysis of the Level of Understanding is that referees and judges in Hulu Sungai Tengah Regency have a good understanding of the latest pencak silat competition regulations and protocols in holding pencak silat matches. Referees and judges must continue to increase their understanding of the latest regulations governing the conduct of matches and the importance of upholding integrity in match fairness, while ensuring that any violations can be dealt with properly. Thus, the researcher recommends to future researchers to carry out training/upgrading as well as carry out pre-tests and post-tests related to understanding the rules of the latest pencak silat competitions. The referees and judges of Hulu Sungai Tengah Regency need to hold something called refreshing as a form of personal upgrade regarding pencak silat regulations.